PENGARUH PENGUNAAN MEDIA PEMBELAJARAN BAGI PROSES PENDIDIKAN SISWA SMP NEGERI 2 KOTA SORONG: THE INFLUENCE OF USING LEARNING MEDIA ON THE EDUCATIONAL PROCESS OF STUDENTS OF SMP NEGERI 2 - KORNELES OHOIWUTUN; Naomi Trogea; Thomson Framonty Elias (EIRENE (JURNAL ILMIAH TEOLOGI), 2023)
Abstract: Basically education, Indonesian education has existed since 1901 during the Dutch occupation of Indonesia and in general education in the 2nd century after the colonial period, early education was formed in families where parents were the first educators before the child became acquainted with the world of education. As for the background of the writer's interest in writing this thesis, it is based on the results of observations and the initial interviews the writer conducted with students and teachers of SMP Negeri 2 Kota Sorong where there are still factors that influence the teaching and learning process. Laziness, student mortality, and the standard of school infrastructure is still limited. The research method used, research method description analysis with data collection techniques, field studies which include observation, interviews and questionnaires. Adapyn in determining the final result uses an analytical technique, namely correlation. Based on the results of the analysis and conclusions in the Discussion chapter, the writer moves away from the creativity of students in class during the teaching and learning process, the teacher is more creative in choosing media during the learning process. So it should be divided again so that it is in accordance with the explanation of the material that is applied during the teaching and learning process.